Pengaruh CAR dan LDR terhadap NPL pada Bank Permata Tbk. Periode 2013-2023 - Tiara Azzahra Aproditha; Hania Bunga Syabina; Agus Supriatna (CV. ITTC INDONESIA, 2025)
The results showed that CAR and LDR had no significant effect on NPL, either partially or simultaneously. This study aims to analyze the effect of Current Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) on Non Performing Loan (NPL) at Bank Permata Tbk during the period 2013 2023. The research method used is quantitative analysis with financial data obtained from the bank's annual report. The data analyzed covers 11 years, resulting in 11 data points for each variable CAR, LDR, and NPL. The results of descriptive statistical analysis show that CAR has an average of 23,273 with a standard deviation of 9,530, while LDR has an average of 81,991 with a standard deviation of 8,098. NPL recorded an average of 1.064 with a standard deviation of 0.6392. Hypothesis testing using regression analysis shows that the F-count value is 0.976 and the significant value (sig.) is 0.418, indicating that there is no significant influence between CAR and LDR on NPL.